Map3k8 controls granulocyte colony-stimulating factor production and neutrophil precursor proliferation in lipopolysaccharide-induced emergency granulopoiesis - Sánchez, Ángela; Relaño, Carlos; Carrasco, Araceli; Contreras Jurado, Silvia Constanza; Martín Duce, Antonio; Aranda, Ana; Alemany, Susana (My University, 2021)
Map3k8 has been proposed as a useful target for the treatment of inflammatory diseases. We show here that during lipopolysaccharide-induced emergency granulopoiesis, Map3k8 deficiency strongly impairs the increase in circulating mature (Ly6GhighCD11b+) and immature (Ly6GlowCD11b+) neutrophils. After chimaeric bone marrow (BM) transplantation into recipient Map3k8¿/¿ mice, lipopolysaccharide treatment did not increase circulating Ly6GhighCD11b+ cells and strongly decreased circulating Ly6GlowCD11b+ cells. Lipopolysaccharide-treated Map3k8¿/¿ mice showed decreased production of granulocyte colony-stimulating factor (G-CSF), a key factor in neutrophil expansion, and a Map3k8 inhibitor blocked lipopolysaccharide-mediated G-CSF expression in endothelial cell lines. Ly6GlowCD11b+ BM cells from lipopolysaccharide-treated Map3k8¿/¿ mice displayed impaired expression of CCAAT-enhancer-binding protein ¿, which depends on G-CSF for expression and is crucial for cell cycle acceleration in this life-threatening condition. Accordingly, lipopolysaccharide-treated Map3k8¿/¿ mice showed decreased Ly6GlowCD11b+ BM cell proliferation, as evidenced by a decrease in the percentage of the most immature precursors, which have the highest proliferation capacity among this cell population. Thus, Map3k8 expression by non-haematopoietic tissue is required for lipopolysaccharide-induced emergency granulopoiesis. The novel observation that inhibition of Map3k8 activity decreases neutrophilia during life-threatening systemic infection suggests a possible risk in the proposed use of Map3k8 blockade as an anti-inflammatory therapy.